Effect unbalance torque training in some biomechanics variables for tack off and landing and long jump achievement - Al Majidi, A. R. J. (Journal of Human Sport & Exercise, 2021)
The Effect Of Unbalance Torque Training In Some Biomechanics Variables For Take-Off And Landing In Long Jump Achievement Sareeh Abudlkareem Abudlsaheeb Alfadly,, Univ. of Baghdad (Iraq) Varying special strength exercises to develop the athlete's abilities in long jump has improved over the years, and yet all these trainings did not take into consideration the importance of the athlete's motor path during phases. This was defined as the problem of this research, which proposed using unbalanced strength moments' training for the working muscles in long jump and gravity moments according to the performance of the two phases. These two phases are closely connected to instant push, acceleration, speed, and mass laws that directly affect biomechanical variables and achievement in youth long jump. Boxes of different heights and angles were used for jumping and added weights on the player to develop the strength of the arms, torso and legs. The aim is to identify the effect of some biomechanical variables of take-off and landing. The experimental method with a training program of three training sessions per week repeated for ten times were used and videotaped the long jump events. After 3 months the post-tests were conducted. The result concluded that these exercises affect the development of speed during the last stride as well as the angle and speed of take-off. Also, the training program develop the angles of attack during take-off and change the momentum and landing biomechanics that are considered important elements in archiving the best distance in long jump. Biomechanics variables for raising the long jump to the pilot group has significant development occurred after tests and impact strength training and control the movements of body parts. The training unbalance force plays an important role in controlling the change of moment of inertia and the angular acceleration. And "most important" Note in the system of levers in human structure is the very high proportion of muscular effort firm resolve that produces against certain resistance. Changing arm lever continuous hinge angle change affects produce such an effect which requires appropriate resistance force change for change in arm strength output owing to changed angle of the joint. This helped development of the efficiency of these muscles through exposure to muscular training effort of all body parts and knives performance and mobility at the same time giving the body's natural qualities as a projectile during the movement (Hang). Also, the strength training unbalance in accordance with torques which resembles as much as possible with performance, transactions carried out with the utmost precision the experimental group with the same motor level in terms of direction and extent of movement of the joint, and movement speed released.